2017
DOI: 10.3390/agriculture7020011
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale Vegetable Farmers’ Participation in Modern Retail Market Channels in Indonesia: The Determinants of and Effects on Their Income

Abstract: Abstract:The rise of supermarkets in Indonesia since the end of the 1990s have been transforming the food retail sector and providing further market opportunities for small-scale farmers, in which most of Indonesia's farmer falls into this category. The aim of this paper is to examine the supermarket participation and its effect on the well-being of small-scale farmers. We compare the differences between participants and non-participants in supermarket channels in order to explore the constraints on supermarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 21 publications
10
31
0
2
Order By: Relevance
“…This is understandable because the farmers’ characteristics represent the quality of human capital. This finding fits studies showing that age and education have a positive impact on the farmer’s choice of market channels (Sahara et al , 2015; Slamet et al , 2017; Zhang et al , 2017). Simultaneously, the farmers’ characteristics encouraged farmers to access credit and utilise the telephone, except for adulthood.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is understandable because the farmers’ characteristics represent the quality of human capital. This finding fits studies showing that age and education have a positive impact on the farmer’s choice of market channels (Sahara et al , 2015; Slamet et al , 2017; Zhang et al , 2017). Simultaneously, the farmers’ characteristics encouraged farmers to access credit and utilise the telephone, except for adulthood.…”
Section: Resultssupporting
confidence: 90%
“…Modern marketing channels include supermarkets, hypermarkets and hospitality industries. Slamet et al (2017) find that when farmers have direct access to modern marketing channels, they got high prices. However, market share for the for fresh horticultural products in the supermarket is meagre and highly competitive.…”
Section: Resultsmentioning
confidence: 99%
“…SAHARA et al (2015) concluded that the supermarket chains pay better for highquality, evenly shaped, and colored products stored in plastic bags or boxes. SAHARA et al (2015), SLAMET et al (2017), andNEVEN et al (2009)opined that family farmers who supply to the supermarkets must use packages that provide better preservation, in addition to owning storage, packaging, and distribution infrastructure. BRANDÃO (2011) stated that one of the retailer chains demanded plastic packages from farmers, attempting to reduce contamination.…”
Section: The Packing and Storagementioning
confidence: 99%
“…Family farmers who work in the fresh fruits and vegetables supply chains face the increasing demand of the modern supply chains regarding the flow of information among the agents. Thus, mobile phones and other communication services are vital for family farmers (SAHARA et al, 2015;SLAMET et al, 2017;DLAMINI-MAZIBUKO et al,2019).…”
Section: Information Exchange Systemsmentioning
confidence: 99%
“…Chromatographic and colourimetric analysis require laboratory support [17]. In situ and real-time methods of laser or sensor are also still ineffective to be applied in food stores or supermarkets that dominantly sell packaged foods [18,19]. ese kinds of foods require a direct indicator on the packaging that provides real-time food quality information.…”
Section: Introductionmentioning
confidence: 99%